Impaired Progesterone-Responsiveness of CD11c+ Dendritic Cells Affects the Generation of CD4+ Regulatory T Cells and Is Associated With Intrauterine Growth Restriction in Mice - Thiele, Kristin; Hierweger, Alexandra Maximiliane; Riquelme, Julia Isabel Amambay; Solano, María Emilia; Lydon, John P.; Arck, Petra Clara (Frontiers in Endocrinology, 2019)
Up to 10% of pregnancies in Western societies are affected by intrauterine growth restriction (IUGR). IUGR reduces short-term neonatal survival and impairs long-term health of the children. To date, the molecular mechanisms involved in the pathogenesis of IUGR are largely unknown, but the failure to mount an adequate endocrine and immune response during pregnancy has been proposed to facilitate the occurrence of IUGR. A cross talk between the pregnancy hormone progesterone and innate immune cell subsets such as dendritic cells (DCs) is vital to ensure adequate placentation and fetal growth. However, experimental strategies to pinpoint distinct immune cell subsets interacting with progesterone in vivo have long been limited. In the present study, we have overcome this limitation by generating a mouse line with a specific deletion of the progesterone receptor (PR) on CD11c+ DCs. We took advantage of the cre/loxP system and assessed reproductive outcome in Balb/c-mated C57Bl/6 PRflox/floxCD11ccre/wt females. Balb/c-mated C57Bl/6 PRwt/wtCD11ccre/wt females served as controls. In all dams, fetal growth and development, placental function and maternal immune and endocrine adaptation were evaluated at different gestational time points. We observed a significantly reduced fetal weight on gestational day 13.5 and 18.5 in PRflox/floxCD11ccre/wt females. While frequencies of uterine CD11c+ cells were similar in both groups, an increased frequency of co-stimulatory molecules was observed on DCs in PRflox/floxCD11ccre/wt mice, along with reduced frequencies of CD4+ FoxP3+ and CD8+ CD122+ regulatory T (Treg) cells. Placental histomorphology revealed a skew towards increased junctional zone at the expense of the labyrinth in implantations of PRflox/floxCD11ccre/wt females, accompanied by increased plasma progesterone concentrations. Our results support that DCs are highly responsive to progesterone, subsequently adapting to a tolerogenic phenotype. If such cross talk between progesterone and DCs is impaired, the generation of pregnancy-protective immune cells subsets such as CD4+ and CD8+ Treg cells is reduced, which is associated with poor placentation and IUGR in mice.